EL LIBRO X DE LAS MET. DE OVIDIO: A PROPÓSITO DE UN RECIENTE COMENTARIO - Fàbregas Salis, Pere (Exemplaria Classica, 2015)
LeeFratantuono, Ovid. Metamorphoses X, London: Bloomsbury, 2014, x + 276 pp., ISBN 978-14-7252-290-0.1